A STRUCTURAL EQUATION MODELLING STUDY ON THE EFFECT OF PROBLEM SOLVING STRATEGIES OF CANDIDATE ENGINEERS ON WORD PHYSICS PROBLEM SOLVING SKILLS - Nilüfer CERİT BERBER (Fırat University, 2019)
The primary purpose in basic physics lessons is to teach students basic physics concept and principles, then to teach them how to use these concepts and principles in problem solving because it is believed that students learn physics as long as they are able to solve physics problems. However, researches conducted on problem solving behavior show that students enter into mathematical details without analyzing problems and they try to remember formulas purposelessly. This situation shows that problem solving behavior in physics lessons itself is a process because solving a physics problem is not only inserting data in a formula. In this process, we encounter strategies which help students in problem solving. For understanding this process, it is important to determine which strategies work for the students by using the problem solving strategies that guide the students in the problem solving process in physics courses besides to determine which problem solving strategies that students use. The purpose of this research is to examine effects of problem solving strategies on solving word physics problems through structural equation modelling. For this purpose, “The Scale of Problem Solving Strategies Used in Physics” was conducted on 195 undergraduates who were studying in different departments of Necmettin Erbakan University Faculty of Engineering and Architecture. Five open-ended word mechanical problems were asked within this scale. The collected data were analyzed using Structural Equation Modelling, which is one of the relational screening models. The results of the research show that the problem solving strategies used in physics including “understanding the problem” and “concentrating on the problem” have considerable effects on word physics problem solving skills.